PENGARUH PERSONAL BRANDING DAN POSITIONING POLITIC TERHADAP PERILAKU MEMILIH PEMILIH PEMULA DALAM PEMILIHAN KEPALA DAERAH KOTA PAYAKUMBUH 2017 ( Studi Kasus Pada Pemilih Pemula di Kecamatan Payakumbuh Barat Kota Payakumbuh Sumatera Barat ) - Ayunda, Indah Permata; Santosa, Edi -; -, Fitriyah - (Journal of Politic and Government Studies, 2018)
Direct elections by the people began in 2005 based on Law No. 32 of 2004 on Regional Government. The behavior of the community can be seen when the community participates in the election, in this context the community's participation in the elections. Part of the voters is the novice selector who in setting options tend to be more bail or easy to change depending on the information obtained. The behavior of choice is influenced by many factors, one of which is personal branding and positioning politic. This study aims to determine the influence of personal branding (X1) and positioning politic (X2) on the behavior of selecting beginner (Y) voters in West Payakumbuh District in the pilkada Payakumbuh 2017.Results and discussion: Quantitative analysis, Personal branding do not affect the behavior of selecting beginner voters while the positioning politic effect. Personal branding and positioning politics influence the behavior of choosing beginner voters. The results of a qualitative analysis, Personal branding effect on the behavior of choosing beginner and positioning politic also influential. Personal branding and positioning politics influence the behavior of choosing beginner voters. Analysis of mix method, personal branding and positioning politics will influence the behavior of selecting beginner voters if done simultaneously.Conclusions and suggestions: Personal branding and positioning politics will influence the behavior of choosing beginner voters if done simultaneously. To obtain maximum results in influencing the behavior of beginner voters Personal Branding and Positioning Politic done simultaneously, both candidates and political party bearers.Â Keywords: Personal Branding, Positioning Politic, Beginner Voters.